Opportunities for renewable energy electrification in remote areas of Costa Rica - Richmond-Navarro, Gustavo; Madriz-Vargas, Rolando; Ureña-Sandí, Noel; Barrientos-Johansson, Fabian (My University, 2019)
Countries around the world are politically driven to move toward a low-carbon future by embracing renewable energies technologies for electricity generation. With abundance of renewable energy resources, Costa Rica has produced over 95% of its electricity from hydro, geothermal and wind power plants. Only 1% of its population live without electricity, mainly in remote territories where rural off-grid electrification is very challenging. The purpose of this research is to understand the opportunities to reach universal electricity access in Costa Rica by using renewables. This paper highlights that a greater level of engagement is needed from local leaders develop efficient solutions. There are more opportunities to access funding schemes if projects are linked with the education sector. Hence, financial and technical support from external entities can be granted supporting the sustainability of the power systems and its expected socio-economic outcomes. This funding scheme can be replicated in other developing countries.
Perspectives on Global Development and Technology. Online Publication Date: 10 Dec 2019
Keywords: Energía renovable; Países en desarrollo; Electrificación; Perspectiva -- Desarrollo; Tecnología; Recursos energéticos; Sostenibilidad; Electricidad; Renewable energy; Developing countries; Electrification; Technology; Energetic resources; Sustainability; Electricity; Research Subject Categories::TECHNOLOGY